DEVELOPMENT OF LECTORA-BASED LEARNING MEDIA IN BASIC CULINARY COURSES TO IMPROVE STUDENT LEARNING OUTCOMES IN THE CULINARY STUDY PROGRAM AT UNIMED - Erli Mutiara; Esi Emilia; Siti Sutanti; Dian Agustina Dalimunthe (Jurnal Ilmiah Teunuleh, 2022)
The aim of this study was to develop learning media for basic culinary course. The study type is study and development using the 4D model, namely define, design, develop, and disseminate. The subjects of this study were 3 media experts, 3 content experts, and 23 students of the culinary education study program. Data collection technique used a questionnaire. Data analysis technique used a descriptive method. The results showed that the Lectora based learning media for culinary course according to content experts was in very good category with an average of 97,64 percent. According to media experts, Lectora based learning media was very good with an average of 94,45 percent. According to users, Lectora based learning media was very good with an average of 94,84 percent. Therefore, it can be concluded that the developed Lectora based learning media for basic culinary course is categorized as very good and can be used as independent learning media for students of the Culinary Education Study Program.